E-Module Teaching Materials Explanatory Texts Containing Noble Morals Using Canva Media for Elementary - Ismail; Kusmana, Suherli; Jaja (International Journal of Educational Research Excellence (IJERE), 2025)
The aim of this study was to develop E-Module teaching materials, Explanatory Text Containing Noble Morals Assisted by Canva Media for Elementary Education,and explain the results of the feasibility test. The research was conducted in the 2023/2024 Academic Year, Even Semester at Madrasah Ibtidaiyah Al-Zaytun, Sandrem Village, Gantar District, Indramayu Regency, West Java Province. This research used the Research and Development (R&D) method withADDIE (Analysis Design Development Implementation and Evaluation) model.Data collection methods include the results of interviews, questionnaires and observations. The research results show thatE-Module teaching materials Explanatory Text Containing Noble Morals Assisted by Canva Media for Elementary a learning teaching material that needs to be developedSo it is hoped that students will be able to absorb and understand the material presented, and have good morals and character.The results of the feasibility test for E-Module teaching materials, Explanatory Texts Containing Noble Morals, Assisted by Canva Media for Elementary by material experts were 82.27% with very feasible criteria, and media experts were 77.08% with appropriate criteria. The feasibility test of E-Module teaching materials for Explanatory Texts Containing Noble Morals with the Assistance of Canva Media for Elementary by practitioners received very good criteria with a score of 90.31%. From the results of the e-module trial on students, the results were 86% with very good criteria.Based on the results of feasibility test research by material experts, media experts, and student responses to the use of e-modules, it can be said that the Canva-assisted Explanatory Text Containing Noble Morals E-Module for Elementary is a teaching material that is suitable for use as a learning medium in the process of teaching and learning activities for teachers and students of class V Elementary, and is expected to make it easier for teachers to convey learning material to students and can help students learn independently